2010
DOI: 10.1097/rlu.0b013e3181e4dd2f
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Gallbladder Metastasis From Non–Small-Cell Lung Cancer Detected by F-18 FDG PET/CT With Intravenous Contrast Enhancement

Abstract: The detection of metastatic disease is important in staging and treatment of lung cancer. Metastatic lung cancer to the gallbladder is rarely reported. We report a case of an initially asymptomatic gallbladder metastasis from lung cancer detected on F-18 FDG PET/CT with intravenous contrast material enhancement. We observed elevated F-18 FDG activity in the gallbladder on PET/CT and subsequently confirmed the diagnosis of metastasis with a percutaneous needle biopsy. F-18 FDG PET/CT can be a useful tool for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Autopsy findings reported by Abrams, et al indicated involvement of the gallbladder in 1.9% of lung cancer patients [2] . To the best of our knowledge, only three cases of clinical NSCLC metastasis to the gallbladder have been reported in the English language literature [3][4][5] Case No.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Autopsy findings reported by Abrams, et al indicated involvement of the gallbladder in 1.9% of lung cancer patients [2] . To the best of our knowledge, only three cases of clinical NSCLC metastasis to the gallbladder have been reported in the English language literature [3][4][5] Case No.…”
Section: Discussionmentioning
confidence: 99%
“…; these cases, along with the present case, are summarized in Table 1. Jeong HT, et al [4] Jeong Y, et al [5] NSCLC: non-small cell lung cancer; NA: not available; TTF-1: thyroid transcription factor-1; CK: cytokeratin; LN: lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the hematogenous diffusion to the gallbladder, GM initially occur as small flat nodules below the mucosal layer and then grow as pedunculated nodules [47]. Usually GM are large hyperechoic (US) or hyperdense broad-based lesions (CT), greater than 1 cm in diameter and rarely associated with gallstones [54][55][56].…”
Section: Lung Cancermentioning
confidence: 99%